Colydodes flavisetis sp. nov. (Coleoptera, Zopheridae, Colydiinae), new species from southeastern Brazil with an updated key to the species of the genus - Ferreira, Vinicius S.; Santos, Guilherme Ide Marques Dos (Zootaxa, 2015)
The species Colydodes flavisetis sp. nov. from southeastern Brazil, at the Biological Station of Boracéia, Salesópolis, São Paulo, is described and illustrated, raising Colydodes diversity from 7 to 8 known species. An updated key to the species of the genus is given.